2018
DOI: 10.3892/ijmm.2018.3799
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase‑2‑mediated upregulation of heme oxygenase 1 mitigates the toxicity of deuterium‑tritium fusion radiation

Abstract: Utilizing the energy released from the nuclear fusion of deuterium with tritium (D-T) may be an important method of supplying energy in the future. The ionizing radiation emitted from nuclear fusion is a potential health risk to humans, including scientists who are currently performing nuclear fusion experiments and the employees of fusion nuclear plants, in the future. However, there have been few reports on the biological effects of fusion radiation. In the present study, using the High Intensity D-T Fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The time course of the transmission and amplification process is unknown, but it is an important parameter in RIBE. Moreover, based on the reports of others [31][32][33][34] and our results, we considered that variations in downstream cellular defense mechanisms might arise depending on the initial levels of PGE2 production.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The time course of the transmission and amplification process is unknown, but it is an important parameter in RIBE. Moreover, based on the reports of others [31][32][33][34] and our results, we considered that variations in downstream cellular defense mechanisms might arise depending on the initial levels of PGE2 production.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, others have reported that COX-2 and PGE2 are potentially involved in the induction of downstream cellular stress defense mechanisms. For example, PGE2 has been shown to induce the oxidative stress defense mechanism by HO-1 activation, which is a downstream gene of Nrf2 via COX-2/PGE2 [31,32]. Also, it is reported that COX-2 expression upregulates defensively against radiation-induced DNA damage and suppression of apoptosis through activation of multiple pathways such as STAT3, HIF-1α/PKM2 pathway [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, HO-1 expression is low in the majority of cells and tissues. Some reports have demonstrated that upregulation of HO-1 is regulated by signaling pathways, in which MAPK kinases play a key role 37,38 . With this in mind, we have evaluated HO-1 levels after 24-and 72-hour treatment with glycofullerenes (Fig.…”
mentioning
confidence: 99%